2017
DOI: 10.1186/s12933-017-0497-7
|View full text |Cite
|
Sign up to set email alerts
|

The renal tubular damage marker urinary N-acetyl-β-d-glucosaminidase may be more closely associated with early detection of atherosclerosis than the glomerular damage marker albuminuria in patients with type 2 diabetes

Abstract: BackgroundTo determine the association between urinary N-acetyl-β-d-glucosaminidase (NAG), a marker of renal tubulopathy, and carotid intima-media thickness (IMT) and plaques in patients with type 2 diabetes mellitus (T2D) and to compare the predictive value of NAG versus albuminuria, a marker of renal glomerulopathy.MethodsA total of 343 participants were enrolled in this retrospective cross-sectional study. We recruited participants with T2D who were tested for blood glucose parameters, urinary NAG, and urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…SGLT2 inhibitors are associated with lower blood pressure and weight loss as well as a reduction in HbA1c levels, changes which in turn have a significant impact on LV function, so that SGLT2 inhibitors may ultimately have a potential beneficial effect on LV diastolic function in patients with T2DM. In addition, it has recently reported that SGLT2 inhibitors have a multifaceted effect on cardiac function including improvement in endothelial dysfunction and aortic stiffness [ 20 ], reduction in epicardial fat accumulation [ 21 ] as well as in visceral adipocyte hypertrophy [ 22 ]. Such effects may well lead to improvement in LV diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors are associated with lower blood pressure and weight loss as well as a reduction in HbA1c levels, changes which in turn have a significant impact on LV function, so that SGLT2 inhibitors may ultimately have a potential beneficial effect on LV diastolic function in patients with T2DM. In addition, it has recently reported that SGLT2 inhibitors have a multifaceted effect on cardiac function including improvement in endothelial dysfunction and aortic stiffness [ 20 ], reduction in epicardial fat accumulation [ 21 ] as well as in visceral adipocyte hypertrophy [ 22 ]. Such effects may well lead to improvement in LV diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…NAG is a lysosomal enzyme of the proximal tubule epithelial cells; due to its large molecular weight, it is not filtered through the glomerulus, and is neither absorbed nor secreted by renal tubules. Unlike other renal function biomarkers that are filtered through the glomerulus, increased urine levels of NAG, deriving exclusively from tubule cells, specifically reflect proximal tubule dysfunction [ 142 , 182 , 183 , 184 , 185 , 186 ]. NAG has been suggested as a more sensitive biomarker of early nephropathy than albuminuria [ 185 , 186 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were some conflicting results, these biomarkers also have shown their associations with CVD; urinary liver-type FABP showed correlations with the development of end stage renal disease and CVD [40]. The association between NAG and CVD was reported mainly in diabetic patients [20,22]. In addition, NGAL and KIM-1 have shown their predictive value for CVD outcomes in various studies [24,25,41].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several tubular damage markers such as fatty acid-binding proteins (FABPs) and N-acetyl-β-d-glucosaminidase (NAG) have gained attention for their correlations with DKD [18,19]. These markers, specific urinary proteins other than albumin, are also associated with other diabetic complications and CVD [20][21][22][23][24][25][26]. These previous studies suggest that even in non-albuminuric T2D patients, there was a significant difference in the risk or status of vascular complications depending on the presence of proteinuria.…”
Section: Introductionmentioning
confidence: 99%